Cowhage-Induced Itch as an Experimental Model for Pruritus. A Comparative Study with Histamine-Induced Itch - Papoiu, Alexandru D. P. (Public Library of Science, 2011)
BACKGROUND: Histamine is the prototypical pruritogen used in experimental itch induction. However, in most chronic pruritic diseases, itch is not predominantly mediated by histamine. Cowhage-induced itch, on the other hand, seems more characteristic of itch occurring in chronic pruritic diseases. OBJECTIVES: We tested the validity of cowhage as an itch-inducing agent by contrasting it with the classical itch inducer, histamine, in healthy subjects and atopic dermatitis (AD) patients. We also investigated whether there was a cumulative effect when both agents were combined. METHODS: Fifteen healthy individuals and fifteen AD patients were recruited. Experimental itch induction was performed in eczema-free areas on the volar aspects of the forearm, using different itch inducers: histamine, cowhage and their combination thereof. Itch intensity was assessed continuously for 5.5 minutes after stimulus application using a computer-assisted visual analogue scale (COVAS). RESULTS: In both healthy and AD subjects, the mean and peak intensity of itch were higher after the application of cowhage compared to histamine, and were higher after the combined application of cowhage and histamine, compared to histamine alone (p<0.0001 in all cases). Itch intensity ratings were not significantly different between healthy and AD subjects for the same itch inducer used; however AD subjects exhibited a prolonged itch response in comparison to healthy subjects ( p<0.001). CONCLUSIONS: Cowhage induced a more intense itch sensation compared to histamine. Cowhage was the dominant factor in itch perception when both pathways were stimulated in the same time. Cowhage-induced itch is a suitable model for the study of itch in AD and other chronic pruritic diseases, and it can serve as a new model for testing antipruritic drugs in humans.